The Shifting Job Tenure Distribution - Henry R. Hyatt; James R. Spletzer (Institute for the Study of Labor (IZA), 2016)
There has been a shift in the U.S. job tenure distribution toward longer-duration jobs since 2000. This change is apparent both in the tenure supplements to the Current Population Survey and the Longitudinal Employer-Household Dynamics matched employer-employee data. A substantial portion of these changes are caused by the ageing of the workforce and the decline in the entry rate of new employer businesses. We show that the tenure distribution is a function of historical hiring rates and tenure-specific separation rates, and we use this framework to show that the shift in the tenure distribution is accounted for primarily by declines in the hiring rate, which are concentrated in the labor market downturns associated with the 2001 and 2007-2009 recessions. We also find that the increase in average real earnings since 2007 is less than what would be predicted by the shift toward longer-tenure jobs; this reflects declines in tenure-held-constant real earnings. Regression estimates of the returns to job tenure provide no evidence that the shift in the job tenure distribution is being driven by better matches between workers and employers.
Keywords: J10; J21; J31; 330; tenure; hires and separations; earnings